PROSECUTORIAL SUPERVISION TOWARDS THE RECEIPT, REGISTRATION AND VERIFICATION OF CRIME REPORTS : Prosecutorial supervision towards the receipt, registration and verification of crime reports - Ghazaryan, Tigraniravaban (State and Law, 2020)
As a result of receiving, registering, inspecting, and preparing materials for criminal reports, the law enforcement agencies allow numerous abuses in practice that directly lead to from on one hand to the violation of the legal interests of the people who presented reports. Alleged victims and on the other hand, to the violation of the rights and legitimate interests of the person who has allegedly committed a crime. Therefore, in order to ensure legality at the stage of initiating criminal proceedings, the legislature has made the activities of the mentioned bodies designated subject to prosecutorial control and judicial supervision, also emphasizing the role and importance of the stage of initiating criminal proceedings. The fixation of the proper mechanisms aims to not only detect and eliminate the legal infringements, but also to prevent them, having as their object the discovery, elimination, prosecution or discovery of groundless denial of initiating a criminal proceeding at the stage of criminal proceedings.